PERAN ZAKAT DALAM MENGENTAS KEMISKINAN - Afifah, Afrah; M. Yarham (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2023)
This article discusses the role of zakat in alleviating poverty. Where zakat is something that is obligatory for the Muslim community. In the Qur'an it is explained that zakat is a responsibility for the Muslim community to help each other. So it can be interpreted that zakat is a moral element. social, educational and economic. In terms of morals, zakat wards off the greed and stinginess of some Muslims who have a sufficient economy. In education, the obligation to give zakat can be taken from the feeling of wanting to give, donate and also give up some of the assets we own as a sign of our love for others. In social matters, namely zakat, the poor can play a role in their lives, carrying out their obligations to Allah SWT, helping with zakat and sadaqah that have been given from people who are capable. As is the case with zakat, underprivileged people feel like they are part of society, or not even outcasts and are looked down upon. In economic terms, zakat can play a role in preventing the accumulation of wealth in the hands of just one person, and also requires rich people to redistribute the wealth they have to rich and poor family groups. So, zakat functions as a potential source of funds in terms of alleviating poverty. Zakat can also be working capital for poor people to open up employment opportunities, so that this group can earn income and also be able to meet their daily living needs. Taken from the feeling of wanting to give, donate, and also give up some of one's wealth as a sign of compassion for fellow humans. In social matters, namely zakat, the poor can play a role in their lives, carrying out obligations to Allah SWT, helping with zakat and sadaqah that have been given from people who are capable. Artikel ini membahas tentang peranan zakat dalam mengentas kemiskinan. Zakat merupakan suatu hal yang diwajibkan bagi umat muslim. Di dalam Al-qur’an dijelaskan bahwa zakat merupakan suatu tanggung jawab bagi umat muslim untuk saling menolong antar sesama. Sehingga dapat diartikan bahwa zakat merupakan unsur moral, sosial, pendidikan, dan ekonomi. Dalam hal akhlak, zakat menepis keserakahan dan kekikiran sebagian umat muslim yang memiliki ekonomi yang cukup. Dalam pendidika,n kewajiban dalam berzakat dapat diambil dari rasa ingin memberi, berinfak dan juga merelakan sebagian  harta yang dimiliki sebagai tanda rasa sayang kita terhadap sesama. Dalam hal sosial, yaitu zakat, golongan miskin dapat berperan dalam kehidupannya, melaksanakan kewajibannya kepada Allah Swt, membantu dalam hal zakat dan sedekah yang telah diberikan dari orang yang mampu. Seperti halnya dengan zakat, masyarakat yang kurang mampu merasa bagian dari anggota masyarakat, atau bahkan bukan orang yang terbuang dan juga diremehkan. Dalam hal ekonomi, zakat dapat berperan dalam hal mencegah penumpukan kekayaan ditangan satu orang saja, dan juga mewajibkan pada orang kaya agar mendistribusikan kembali kekayaan yang dimilikinya kepada golongan keluarga kaya dan juga miskin. Jadi, fungsi zakat  sebagai sumber dana potensial dalam hal untuk mengentasi kemiskinan. Zakat juga bisa menjadi modal kerja untuk masyarakat miskin untuk  membuka lapangan pekerjaan, sehingga golongan tersebut dapat memperoleh penghasilan dan juga mampu memenuhi  kebutuhan hidup sehari-hari. Diambil dari rasa ingin memberi, berinfak, dan juga merelakan sebagian hartanya sebagai tanda rasa kasih sayang sesama manusia. Dalam hal sosial, yaitu zakat, golongan miskin dapat berperan dalam kehidupannya, melaksanakan kewajiban kepada Allah Swt, membantu dalam hal zakat dan sadaqah yang telah diberikan dari orang yang mampu.